DARK ROMANCE: VIOLENCE AND EROTICISM IN THE NUN AND THE MOBSTER (2021) BY FIC DARK (Interdisciplinary Studies Journal, 2026)
This article investigates the representation of the constitutive elements and narrative structure of the Dark Romance genre in the novel A freira e o mafioso (2021), by Fic Dark. Originally published on the Wattpad platform, the story follows Clara, an orphan aspiring to a religious life, and Maximus, an Italian mafia leader, whose relationship is marked by tensions involving self-discovery, abuse of power, submission, and the symbolic conflict between good and evil. Drawing on the studies of Fajardo (2023), the analysis examines how Dark Romance articulates eroticism and violence as narrative strategies to intensify dramatic tension and foster character development. The central objective is to understand how this subgenre mobilizes the intensity of human emotions while simultaneously challenging the traditional conventions of the romance genre, in line with the reflections of Dekel (2013). In this sense, the study highlights the role of eroticism and violence as structuring axes of the narrative typical of Dark Romance.
Keywords: Dark Romance; Violence; Erotism; Literary Analysis; A Freira e o Mafioso